Screen Time and Psychological Well-Being among Children: The Moderating Effect of Parenting Styles - Mohtaram, Rabbani; Simin, Hosseinian; Nur Hidayah, Zulkharnain (UNIMAS Publisher, 2022)
Children nowadays are reported to have low psychological well-being when exposed to too much screen time. Children usually imitate their parents' or adults' behaviour towards screen time or gadgets usage. Parents who spend too much screen time result in excessive screen time in their children, which leads to various problems in their social and cognitive development. This study aims to determine how parenting styles affect children's screen time and psychological well-being. In this context, screen-time is the amount of time spent on gadgets with the screen to watch videos, movies, or play games. To test the hypothesis that the amount of screen time does affect children's psychological well-being, an online survey was distributed and circulated among parents or primary caregivers staying in Kuala Lumpur and taking care of a child aged 3-6 years old. A series of questionnaires, including ones on demographic data, parenting style and domains, and strengths and challenges, are included in the survey. The analysis was conducted using Pearson correlation and multiple regression analysis in SPSS. There was a significant correlation between the amount of screen time and psychological well-being. The relationship between parenting style and the amount of screen time was not significant. Next, the interaction between the amount of screen time and parenting style was found to be not significant. Hence, the study concludes that parenting style does not affect the relationship between children's screen time and psychological well-being.